Development of an Economics E-Module Based on Differentiation in the Merdeka Curriculum Using iSpring Suite for Grade XI Senior High School Economics Subject in Babat, Lamongan - Alifia, Atika; Susanti, Susanti; Wulandari , Siti Sri (IKIP PGRI Bojonegoro, 2025)
The transformation of education in the digital era demands innovative teaching media that adapt to students' diverse learning styles. This study aims to develop, validate, and evaluate the effectiveness of a differentiated economics e-module using iSpring Suite, tailored to the Merdeka Curriculum for Grade XI senior high school students in Babat, Lamongan. The research employed the 4D development model (Define, Design, Develop, Disseminate), combined with a quasi-experimental approach using a one-group pretest-posttest design. Data collection instruments included expert validation questionnaires, student response questionnaires, and learning outcome tests. The findings indicate that the e-module received very high feasibility ratings from subject matter, media, and language experts. Student responses reflected a high level of practicality and engagement. The paired-samples t-test showed a significant difference between students’ pretest and posttest scores, indicating that the e-module effectively enhanced learning outcomes. It can be concluded that this e-module is effective in improving students’ learning achievements and motivation, and provides a positive contribution to the implementation of technology-based differentiated learning in the Merdeka Curriculum.